On super edge-magic total labeling of banana trees - Hussain M.; Baskoro E.T.; Slamin (Utilitas Mathematica, 2022)
Let G1, G2,..., Gn be a family of disjoint stars. The tree obtained by joining a new vertex a to one pendant vertex of each star Gi is called a banana tree. In this paper we determine the super edge-magic total labelings of the banana trees that have not been covered by the previous results [15].